Transforming English Speaking Skills in Phenomenological Studies in Indonesia - Aprilia, Friska; Santoso, Dian Rahma (Education and Development Research, 2024)
Abstract: This study investigates the challenges faced by English teachers in teaching speaking skills in state junior high schools in Sidoarjo, Indonesia, particularly in the post-pandemic era. Through interviews and class observations with three experienced teachers, the research identifies student-related challenges such as lack of participation, slow speech, and limited vocabulary, as well as teacher-related challenges including curriculum constraints and limited English proficiency. The findings highlight the need for innovative teaching strategies and curriculum adaptations to improve students' speaking proficiency. This research fills a knowledge gap by offering insights into the specific challenges of teaching speaking in an EFL context post-pandemic and suggests avenues for future research to deepen understanding and develop effective solutions. Abstrak: Penelitian ini menyelidiki tantangan yang dihadapi oleh guru bahasa Inggris dalam mengajarkan keterampilan berbicara di sekolah menengah pertama negeri di Sidoarjo, Indonesia, khususnya di era pasca pandemi. Melalui wawancara dan observasi kelas dengan tiga guru yang berpengalaman, penelitian ini mengidentifikasi tantangan yang berhubungan dengan siswa seperti kurangnya partisipasi, lambatnya berbicara, dan terbatasnya kosakata, serta tantangan yang berhubungan dengan guru termasuk kendala kurikulum dan kemampuan bahasa Inggris yang terbatas. Temuan ini menyoroti perlunya strategi pengajaran yang inovatif dan adaptasi kurikulum untuk meningkatkan kemampuan berbicara siswa. Penelitian ini mengisi kesenjangan pengetahuan dengan menawarkan wawasan tentang tantangan spesifik pengajaran berbicara dalam konteks EFL pasca pandemi dan menyarankan jalan untuk penelitian di masa depan untuk memperdalam pemahaman dan mengembangkan solusi yang efektif.